Forcing the Immovable One to the Ground: Revisioning a Major Deity in Early Modern Japan - Bond, Kevin A. (My University, 2009)
This dissertation examines early modern (seventeenth-mid-nineteenth century) Japanese religion through a study of a cult devoted to the popular deity Fudō Myōō ("The Immovable King of Illumination") at Naritasan Temple (also known as Shinshōji Temple) in Shimōsa Province (present-day Chiba Prefecture). It discusses how Naritasan developed a distinctive corpus of miracle tale literature centered around its sacred statue of Fudō, and how these tales interwove doctrinal and sectarian traditions with local geography and history to produce a regionally-specific brand of the deity. This process of individuation became central to the creation of Naritasan's identity and religious activities, its promises of material and spiritual rewards, and to the way stories were used to spread the cult among the populace through recreational and commercial enterprises. I demonstrate how these narratives can thus be read in light of the temple's evolution and socio-economic changes affecting early modern Japan as a whole. By employing a locally-based and trans-sectarian approach to the study of the Fudō cult at Naritasan, this dissertation seeks to illuminate a number of issues: how the temple used miracle tales to domesticate and transform Fudo into a trademark "Narita Fudō", a process central to the religious and commercial identities of temples; how the Narita Fudo was not static but evolved over time to became an object of worship shared across a variety of religious and popular traditions; and finally, how the deity therefore resists convenient categorizations afforded him by modern scholarship, thus challenging the ways we understand one of Japan's oldest and most important deities.
Keywords: Japanese religion; Fudō Myōō; Japanese deity; Naritasan Temple; miracle tale literature